Acute effects of different types of stretching exercises on explosive power: A pilot study - Sinan Seyhan; Emirkan Çelik (Turkish Journal of Kinesiology)
Athletes usually use warm-up and stretching exercises before starting a vigorous physical activity. The aim of this study was to investigate the positive and negative effects of different stretching and flexing exercises on kicking acceleration performance in taekwondo. A total of 12 elite taekwondo athletes (7 boys and 5 girls) with an average age of 20.75±1.48 years, an average height of 171±10.06 cm, an average body weight of 61.8±11 kg, and an average Body Mass Index (BMI) of 21.1±2.5 kg/m2 participated in this study. For the kick acceleration test (KAT), an accelerometer was used by attaching it to the ankle of the participants with the help of a smart phone and a smart watch. For KAT measurements, static stretching exercise (SSE), dynamic stretching exercise (DSE), proprioceptive neuromuscular facilitation exercise (PNFE) and ballistic stretching exercise (BSE) methods were applied on different days during the warm-up phase. In this study with elite level Taekwondo athletes, significant differences were found between palding chagi and dollyo-chagi kick acceleration values after SSE and PNFE applications (p